Eco-innovation: the profile of Poland in comparison to the European Union - Z. Ostraszewska; A. Tylec (Global Journal of Environmental Science and Management)
Innovativeness, determining the development potential of enterprises and economies, and hence the economic welfare of societies, became an important area of interest for both theoreticians and especially economic life practitioners. Thus, in this study of the subject there can be found numerous definitions and types of innovation, including environmental innovation, being a response to the demands of a modern economy, related to the need of combining innovativeness with care for the environment. The observed increase of interest in the idea of sustainable development, and often some kind of reorientation of enterprises towards the eco-innovative strategy, are associated with the perception of the eco-innovation as both a necessity and a chance for promotion and development. Despite this, only less than 1/3 of the countries belonging to the EU can be considered as innovative and eco-innovative at the same time. Poland still does not belong to these countries - on the map of the EU innovation Poland ranks among the so-called moderate innovators (with the SII index of 0.27 in 2017, while the EU index was 0.504). With the Eco-IS score equal to 59 the level of eco-innovativeness of the Polish economy is much below the EU average (Eco-IS = 100) – in 2017 Poland obtained 26th place out of 28 European Union countries. Given the above, this paper outlines the nature of eco-innovativeness with particular focus on the results recorded by Poland in this regard in comparison to the European Union.